Decoronation as an option for ridge preservation prior to implant placement - Dragović Miroslav; Pejović Marko; Stepić Jelena; Dragović Svetlana; Čolić Snježana (Serbian Medical Society - Dental Section, Belgrade, 2017)
Decoronation is a surgical procedure based on idea of sectioning tooth crown and maintaining the root in situ with intention to preclude occurrence of severe deformities of bone and soft tissue which may aggravate later rehabilitation of patient. The aim of this report is to present the use of decoronation in a young adult patient as a solution in order to preserve sufficient amount of bone for delayed implant placement and decrease volume of grafting material to a minimum. Obtained results showed this procedure may greatly improve anatomical conditions for implant placement while reducing invasiveness and required financial means.